How do proteins fold and why? - Englander, Walter (Henry Stewart Talks, 2007)
Challenges to studying protein folding, Methods based on hydrogen exchange (HX), Foldon units, Step-wise assembly, Building the native protein, Error-dependent misfolding steps, Role of chaperone molecules, Other roles for Foldon behavior
Reviewed at 2022/04/12